The Psychoanalytic Analysis of Low Self-Esteem on the Movie The Ron Clark Story - Wuri Widiastiti; Dian Maya Kurnia; Sufil Lailiyah (Pioneer: Journal of Language and Literature, 2019)
Low self-esteem is unworthy feeling because of less attention, love, affection and trust. The impact of low self-esteem could make negative feeling. It is not only to their own life, but also to their surrounding society. Low self-esteem can also be triggered by mistakes that came from parents, family, society and also teacher. The worst effect of low self-esteem in adolescence is on their academic score. They will get bad score because they do not have self confidence to do the assignment or try new experiences. This research purposed to find the low self-esteem, the factor of low self-esteem and the problem solving which is found in the action, gesture and utterance of main characters in the movie The Ron Clark Story. This research used descriptive qualitative research, because the researcher described the data that portray of low self-esteem. The researcher analyzed the data by using psychoanalytic analysis approach from Sigmund Freud. The data was analyzed by describing the low self-esteem in the movie The Ron Clark Story based on Tyson’s theory and the problem solving from Lachmann and Ron Clark’s theory. The researcher found 40 data of low self-esteem that showed in the movie The Ron Clark Story. The dominant factor was the academic challenges without caregiver’s support. The problem solving based on the movie The Ron Clark Story were classified into eight components. The most important component was implementing the class’s rules, followed by giving an appreciation, attention, care, trust, motivation, and help when they get difficulties, making innovation teaching method (especially for the teacher). Cooperation between parents and teachers are very important for the growth of the self-esteem and worthy to get the best potential of children’s life.